Penerapan Efektivitas Hukum Lingkungan di Indonesia: Penelitian - Wilma Silalahi; Marsalina Susana (PT PUSTAKA CENDEKIA GROUP, 2025)
Environmental law enforcement under Law Number 32 of 2009 is both preventative and repressive. Preventive efforts to control environmental impacts must be implemented by maximizing the use of monitoring and licensing instruments, which can be implemented by the central government, regional governments, and the community. Repressive efforts are carried out when environmental pollution and destruction have already occurred, either through administrative, civil, or criminal legal instruments. Implementation of sustainable development and the controlled use of natural resources is the goal of environmental management . Environmental management issues can be considered as one of the main causes of environmental damage . The goal of all environmental problems are done without regard to the development of the environmental factors, which in turn will cause environmental damage and pollution. Given the legal action against the perpetrators of pollution and environmental destruction is composed of administrative aspects, aspects of civil, criminal aspects. In the law enforcement itself should be supported pleh several factors, namely the means of law, law enforcement personnel, facilities and infrastructure, licensing, EIA system, public awareness of the environment.